Growth of textured superconducting layer of YBa2Cu3O7 on perovskite single crystal substrates - González, J. C. (2012)
The route by chemical solution deposition to grow textured layers of oxide superconductors has received the most scientific attention over the past two decades. Texture plays a predominant role in the technological applications of superconducting layers. We crystallized a precursor solution of Y, Ba and Cu acetates onto single crystal substrates of perovskite structure by the route of chemical solution deposition and we obtained textured superconducting layers of YBa2Cu3O7. We divided our results in two parts: a) We review the epitaxial growth of YBa2Cu3O7 superconducting layers through physical and chemical methods, and b) We study mainly the epitaxial growth of YBa2Cu3O7 superconducting layers by X ray diffraction.